1988
DOI: 10.1002/jsfa.2740430204
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds in coffee pulp: Quantitative determination by HPLC

Abstract: The content of phenolic compounds tentatively identifed by HPLC in fresh coffee pulp gives an average composition in the 12 cultivars studied as follows: chlorogenic acid (5-caffeoylquinic acid), 42.2%; epicatechin, 214%; isochlorogenic acid I, 5.7%; isochlorogenic acid II, 19.3%; isochlorogenic acid III, 4.4%; catechin, 2.2%; rutin, 2.1 %; protocatechuic acid, 1.6%; and ferulic acid, 1.0%. When the percentages of chlorogenic and isochlorogenic acids are added to the corresponding one of epicatechin for each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
18

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 21 publications
2
43
1
18
Order By: Relevance
“…Os teores de cafeína encontrados neste estudo estão de acordo com os mínimos (0,48%) e máximos (1,31%) encontrados na literatura (BRESSANI, ES-TRADA e JARQUIN, 1972;JARQUIN et al, 1973;VARGAS et al, 1982;Ramirez-Martinez, 1988) Tam Pela análise estatística não foram verificados efeitos de cultivares (P≥0,94) e de material (P≥0,73), indicando que tanto a casca (0,87%) quanto a polpa (0,86%) e as cultivares Catuaí (0,87%), Rubi (0,87%) e Mundo Novo (0,86%) apresentaram teores de cafeína semelhantes (Tabela 1).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os teores de cafeína encontrados neste estudo estão de acordo com os mínimos (0,48%) e máximos (1,31%) encontrados na literatura (BRESSANI, ES-TRADA e JARQUIN, 1972;JARQUIN et al, 1973;VARGAS et al, 1982;Ramirez-Martinez, 1988) Tam Pela análise estatística não foram verificados efeitos de cultivares (P≥0,94) e de material (P≥0,73), indicando que tanto a casca (0,87%) quanto a polpa (0,86%) e as cultivares Catuaí (0,87%), Rubi (0,87%) e Mundo Novo (0,86%) apresentaram teores de cafeína semelhantes (Tabela 1).…”
Section: Resultsunclassified
“…Esses estudos indicam a presença de alguns componentes que interferem na utilização da polpa como alimento para ruminantes. Compostos como cafeína e taninos têm sido indicados como possíveis fatores antinutricionais da polpa, mas sem evidências conclusivas que apóiem esta afirmativa (RAMIREZ-MARTINEZ, 1988). BARCELOS et al (1997a) e BARCELOS et al (1997b encontraram teores de 1,83 e 1,29% de taninos e 0,86 e 0,81% de cafeína, enquanto Ribeiro Filho (1998) encontrou teor de 2,08% para os compostos fenólicos totais da casca de café e 0,97% para cafeína.…”
Section: Introductionunclassified
“…In fact, caffeine is 1.5% ofthe coffee solids and is the only coffee chemical that is extracted and marketed around the world, mainly as a low price additive for cola drinks. Thanks to the pioneer work done at the University of Zulia in Venezuela, we now have a more clear picture of the types of chemicals in coffee cherries and pulp (Clifford, 1979;Ramirez-Martinez, 1988;Clifford and Ramirez-Martinez, 1991;De Colmenares et al, 1994, 1998. It has been found that the main contribution to phenolic compounds in the coffee beans and pulp are, chlorogenic acid, 42.2%, epicatechin, 21.6%, isochlorogenic acid I, 5.7%, isochlorogenic acid II, 19.3% (Ramirez-Martinez, 1988).…”
Section: Coffee Pulp As a Source Of New Materials (Antioxidants And Amentioning
confidence: 96%
“…Thanks to the pioneer work done at the University of Zulia in Venezuela, we now have a more clear picture of the types of chemicals in coffee cherries and pulp (Clifford, 1979;Ramirez-Martinez, 1988;Clifford and Ramirez-Martinez, 1991;De Colmenares et al, 1994, 1998. It has been found that the main contribution to phenolic compounds in the coffee beans and pulp are, chlorogenic acid, 42.2%, epicatechin, 21.6%, isochlorogenic acid I, 5.7%, isochlorogenic acid II, 19.3% (Ramirez-Martinez, 1988). Also, condensed tannins are abundant in the coffee pulp from fresh cherries but they polymerise rather quickly after drying due to spontaneous oxidation (De Colmenares et at., 1994).…”
Section: Coffee Pulp As a Source Of New Materials (Antioxidants And Amentioning
confidence: 96%
“…From the chlorogenic acids family (caffeoylquinic acids), the most reported isomers are, 3-CQA, 4-CQA and 5-CQA. 5-CQA is the most abundant compound found in coffee beans, responsible for about 56-62 % of total chlorogenic acids (Ramirez-Colonel et al, 2004, Ramirez-Martinez 1988. It is also the most abundant antioxidant in coffee foliage (Marques, 2011).…”
Section: Introductionmentioning
confidence: 99%